HUBUNGAN RISIKO DAN RETURN SAHAM PADA PERUSAHAAN YANG TERKENDALA KEUANGAN DAN TIDAK TERKENDALA KEUANGAN (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BEI) - , Swandita Adinata, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study examined the effect of financial constraints condition to the relation between past stock return with the current volatility of stock returns in manufacturing companies listed in Indonesia Stock Exchange (IDX) at the years 2005-2009. Financial constraints are circumstances when a company is not able to obtain funding from external sources to finance new investments. This study argues that the relation the company's past stock return has a negative relation with current stock return volatility. Negative relation is appear because of asymetric information condition whose boost reactive attitude of investors in anticipation of future risk. Stock risk in this study indicated the presence of company stock return volatility. The results of this study indicate that there are negative relation between past stock return and current volatility of stock returns. However, the relation between past stock returns with the current firm stock return volatility do not have a significant negative relation despite the known risks of the financially constraint company's stock are higher. But financial constraints company condition do not affect relation between past stock return with the current volatility of stock return.